Efektivitas Teori Sibernetika Pada Mata Pelajaran Bahasa Indonesia Tingkat Sekolah Dasar di “Ruangguru” - Azis, Moch Qitfirul; Wiryanto, Wiryanto; Muhimmah, Hitta Alfi (Universitas Negeri Makassar, 2023)
The study alms to determine the effectiveness of cybernetics theory in Indonesian subjects at the elementary school level and to formulate a cybernetic strategy in a space effort to apply learning to students about cybernetics theory. This research is a qualitative research using descriptive methods. Interviews and documentation. The results of the study show that learning chybernetics theory in elementary schools is effective if accompanied by parents, this is because renters have net been able to access digital technology properly startup digital “Ruangguru” can be used as a means of independent learning in schools. Theory and concepts about learning the context of reading, writing and listening is fully available. Howevwr, speaking practice materials for self development are not well facilitated. The role of educators in shapping the attitudes and morals of students also cannot be represented by simply being applied online. It can be conculeded that startup digital “Ruangguru” as distance learning methods are only used to increase knowledge.